2023
DOI: 10.3390/s23042039
|View full text |Cite
|
Sign up to set email alerts
|

Driver Attention Assessment Using Physiological Measures from EEG, ECG, and EDA Signals

Abstract: In this paper, we consider the evaluation of the mental attention state of individuals driving in a simulated environment. We tested a pool of subjects while driving on a highway and trying to overcome various obstacles placed along the course in both manual and autonomous driving scenarios. Most systems described in the literature use cameras to evaluate features such as blink rate and gaze direction. In this study, we instead analyse the subjects’ Electrodermal activity (EDA) Skin Potential Response (SPR), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…HR and EDA are sensitive to changes in arousal and, thereby, are also associated with changes in attention. Indeed, HR and EDA respond to arousing, emotionally relevant events that are attentionally prioritized [ 15 , 16 ] and contribute to the monitoring of driver attention [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…HR and EDA are sensitive to changes in arousal and, thereby, are also associated with changes in attention. Indeed, HR and EDA respond to arousing, emotionally relevant events that are attentionally prioritized [ 15 , 16 ] and contribute to the monitoring of driver attention [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was designed to induce high and low mental engagement in drivers through manual and autonomous driving tasks, respectively. This approach was chosen based on our previous research findings, which showed that manual driving elicits higher mental engagement compared to autonomous driving, and these differences can be detected through EEG, SPR, and ECG signals [36,37]. Accordingly, to represent high engagement, a label of "0" was assigned to all manual driving segments, while a label of "1" was assigned to all autonomous driving segments, representing low engagement.…”
Section: Signal Segmentationmentioning
confidence: 99%
“…The power spectral density was calculated by the Lomb-Scargle periodogram [60]. Based on original research articles [31,[35][36][37]42,47,[61][62][63], 14 HRV features listed in Table 1 that might be the potential to differentiate concentration and distraction were computed.…”
Section: Physiological Signal Preprocessing and Feature Computationmentioning
confidence: 99%